MBL1 gene in nonhuman primates. - Segat, Ludovica; Crovella, Sergio (Hum Immunol, 2011)
With the aim of investigating the evolution of MBL1P1 (MBL1) gene, we analyzed the MBL1 coding region sequences in several specimens of two species of great apes, two species of Hylobatidae, four species of Cercopithecidae, and one Platyrrhine species, and in human beings. An indication for a progressive silencing of the molecule has been found. We found a ∼300 bp insertion in the first intron of MBL1 in the Cercopithecidae that could explain the different splicing between primates species and possibly why Macaca mulatta is able to produce a complete protein, whereas in human beings the protein product is truncated. Based on our genetic findings, we could speculate that all the Cercopithecidae (presenting the 300-bp insertion) may express MBL1 mature protein like the M mulatta, whereas the lesser and great apes, which lack this insertion as do human beings, may have only the truncated pseudogene.
Keywords: Animals; Base Sequence; Evolution, Molecular; Gene Silencing; Genome; Humans; Mannose-Binding Lectin; Molecular Sequence Data; Multigene Family; Phylogeny; Polymorphism, Genetic; Primates; Pseudogenes; Sequence Alignment; Sequence Analysis, DNA; Sequence Deletion; Species Specificity